A thermophysically balanced multiscale coarse-grained potential for glass-forming polymers with the energy renormalization method. (24th February 2021) - Jung, Jiwon; Park, Chanwook; Yun, Gun Jin
Abstract: Coarse-grained molecular dynamics simulations are a widely accepted methodology in the field of studying the viscoelasticity of elastomers. In this paper, a thermophysically balanced multiscale coarse-grained potential for glass-forming polymers is presented with the energy renormalization (ER) method by redefining temperature transferable correlation effects between rescaling factors for energy parameter and length-scale parameter. The correlation effects have not been investigated in the literature, to the best knowledge of authors. The coarse-grained potential was demonstrated for the polyisoprene model generated from the anionic polymerization. The ER enables temperature transferability by adopting renormalization parameters as function of the temperature. Considering the correlation effects, a multi objective-optimization algorithm was adopted to find proper solution sets of α and β matching mean square displacement (MSD) and density to the all-atom model simultaneously. Meanwhile, shear stress was matched to find α first, then, density was fitted in the low-temperature regime. To verify the coarse-grained potential in the middle-temperature regime, MSD was compared to those from the all-atom model, and it was successfully matched.